Agreement between pediatrician and trained paramedic in the assessment of gestational age among newborns using New Ballard Scored - Tunjung Wibowo, Henky Sulistyo Djauhar Ismail (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2011)
Accurate gestational age assessment is important in newborn examination to determine further management. Oneof methods to estimate newborn gestation is New Ballard Score (NBS). With limited number of pediatrician especiallyin remote areas, it is expected trained paramedic will be able to perform NBS examination properly. The aim of thisstudy was to assess whether there is agreement between pediatricians and trained paramedics in determiningnewborn gestational age using NBS. This was a cross sectional study. Ballard scoring was performed by pediatriciansand trained paramedics in Dentatama Mother and Child Hospital, Sragen Distric, Central Java, Indonesia fromFebruary-May 2008. Statistical analysis was performed using intraclass correlation. This study was performed in175 newborns those consisted of 55.4% males and 44.6% females. From those newborns, 30.3% were deliveredby caesarian section, and 10.3% were premature baby. Majority of Ballard score examination (69.7%) was performedin 2nd day. According to intraclass correlation, there was a very strong correlation agreement between pediatriciansand trained paramedics (r=0.925 and p<0.05). The result of Ballard score examination that close to gold standardthose which were performed at 48-96 hours of age (r=0.993 and p<0.05). In conclusion, there was a goodagreement between pediatricians and trained paramedics in assessing newborn gestational age using NBS.Key words: Ballard score - trained paramedic - newborn â pedriatician - hospital